2011
DOI: 10.1186/1472-6963-11-127
|View full text |Cite
|
Sign up to set email alerts
|

Nurse prescribing of medicines in Western European and Anglo-Saxon countries: a systematic review of the literature

Abstract: BackgroundA growing number of countries are introducing some form of nurse prescribing. However, international reviews concerning nurse prescribing are scarce and lack a systematic and theoretical approach. The aim of this review was twofold: firstly, to gain insight into the scientific and professional literature describing the extent to and the ways in which nurse prescribing has been realised or is being introduced in Western European and Anglo-Saxon countries; secondly, to identify possible mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
211
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(225 citation statements)
references
References 107 publications
(420 reference statements)
2
211
1
7
Order By: Relevance
“…Prescribing to patients was the exclusive role of doctors and dentists, until the introduction of non-medical prescribing (NMP) in some countries which allowed non-medical professionals including nurses and pharmacists to prescribe medicines [2,3]. A number of countries have legislated for NMP including the United States of America (USA), United Kingdom (UK), Australia, New Zealand, Canada, Sweden, Republic of Ireland, South Africa, Botswana, Kenya and Uganda [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing to patients was the exclusive role of doctors and dentists, until the introduction of non-medical prescribing (NMP) in some countries which allowed non-medical professionals including nurses and pharmacists to prescribe medicines [2,3]. A number of countries have legislated for NMP including the United States of America (USA), United Kingdom (UK), Australia, New Zealand, Canada, Sweden, Republic of Ireland, South Africa, Botswana, Kenya and Uganda [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, national studies of supplementary prescribing (Bissell et al, 2008) mental health nurse prescribing (Norman et al, 2010) and independent prescribing in Ireland (Naughton et al, 2013) all showed largely positive findings, and so helped build support and confidence for nurse prescribing in the UK. Studies demonstrate that the prescription of medication by nurses is safe and competent, has led to better access and quality of care for patients, improvements in the abilities and experience of nurses, increased professional recognition, the legitimation of responsible autonomous practice and enabled better team working between the various healthcare professionals (Latter et al, 2012;Kroezen et al, 2011;Bhanbhro et al, 2011). Kroezen et al (2011) state that patient support and grassroots legislative constituency are crucial in battles over prescribing rights and these UK national studies all consistently reported patient support for nurse prescribing.…”
mentioning
confidence: 99%
“…Studies demonstrate that the prescription of medication by nurses is safe and competent, has led to better access and quality of care for patients, improvements in the abilities and experience of nurses, increased professional recognition, the legitimation of responsible autonomous practice and enabled better team working between the various healthcare professionals (Latter et al, 2012;Kroezen et al, 2011;Bhanbhro et al, 2011). Kroezen et al (2011) state that patient support and grassroots legislative constituency are crucial in battles over prescribing rights and these UK national studies all consistently reported patient support for nurse prescribing. In Brazil there is no research that has evaluated the impact, quality or safety of the prescription of medication by nurses in primary health care, and this is now urgently required in order to collate evidence that may help win support and legitimacy for taking it forward.…”
mentioning
confidence: 99%
See 2 more Smart Citations